Концептуальный подход к формированию стратегий развития моногородов в контексте исследования процесса урбанизации (Вестник КазНУ. Серия Экономическая, 2023)
The modernization of monocities occupies an important place in the socio-economic development of the country, which increases the importance of the issues of research, analysis and monitoring of their functioning. Therefore, the development of strategic solutions for the revival of monocities in terms of new approaches to their development is an urgent issue. The purpose of the study is to form a conceptual approach to the modernization of monocities in the Republic of Kazakhstan, which will reflect a consistent subject area for building strategies for their development. To study these issues, a peer review method was chosen among two groups: scientific researchers and expert practitioners. Data evaluation was carried out through statistical (mean value, index method), factorial (weight coefficient and concordance), and matrix analysis based on Microsoft Excel software. The developed conceptual approach, as a methodological guide to the transformation of monocities, will allow defining its elements in the form of goals, problems, factors, conditions and processes, as well as internal and external relations in the development of development strategies for the object of study. The practical significance lies in the need for local authorities to introduce the proposed conceptual approach to solve the problems of monocities development. This article is valuable for future research on the formation of strategic decisions for the modernization of monocities that determine their future development.